Ka-Band Slot-Microstrip-Covered and Waveguide-Cavity-Backed Monopulse Antenna Array - Li-Ming Si; Yong Liu; Yongjun Huang; Weiren Zhu (International Journal of Antennas and Propagation)
A slot-microstrip-covered and waveguide-cavity-backed monopulse antenna array is proposed for high-resolution tracking applications at Ka-band. The monopulse antenna array is designed with a microstrip with 2×32 slots, a waveguide cavity, and a waveguide monopulse comparator, to make the structure simple, reduce the feeding network loss, and increase the frequency bandwidth. The 2×32 slot-microstrip elements are formed by a metal clad dielectric substrate and slots etched in the metal using the standard printed circuit board (PCB) process with dimensions of 230 mm  ×  10 mm. The proposed monopulse antenna array not only maintains the advantages of the traditional waveguide slot antenna array, but also has the characteristics of wide bandwidth, high consistence, easy of fabrication, and low cost. From the measured results, it exhibits good monopulse characteristics, including the following: the maximum gains of sum pattern are greater than 24 dB, the 3 dB beamwidth of sum pattern is about 2.2 degrees, the sidelobe levels of the sum pattern are less than −18 dB, and the null depths of the difference pattern are less than −25 dB within the operating bandwidth between 33.65 GHz and 34.35 GHz for VSWR ≤ 2.